Literature Review of Safety Event Reporting in Observational Studies: Challenges Extrapolating across Comparable Products - Heather A. Ward; Bao-Anh; Robert Massouh (MDPI AG, 2023)
Nirmatrelvir/ritonavir (PAXLOVIDTM, Pfizer) is an anti-infective inhibiting CYP3A4 indicated for the treatment of COVID-19 in adults at increased risk of severe COVID-19. As a newly approved product, PAXLOVID has limited safety information regarding rare events and serious adverse events (SAEs). This review describes the characterization of the real-world safety profile of products with similar pharmacological properties to PAXLOVID and aims to understand the impact of any drug interaction on the concomitantly prescribed products. A literature search of articles in PubMed published between 2018 and 2023 was conducted to assess the real-world frequency of safety outcomes of interest, specifically those meeting the criteria of serious adverse reaction. The review was restricted to observational, noninterventional studies and included CYP3A4 inhibitors prescribed for short-term treatment of infections in the outpatient setting. Twenty-one articles were included in the review. Most focused on a small, predefined list of safety outcomes and did not provide insight into the broader range of safety outcomes that might occur for the evaluated products with similar pharmacological properties to PAXLOVID or the impact of any interaction on the concomitant product. The findings highlight the challenges in obtaining proxy safety outcomes characteristics via a review of products with comparable pharmacological properties and underscore the need to have large, rapidly accessible data sources that can contribute to the safety profile of newly authorized products in the real world.